Agreement between mechanical and digital skinfold callipers - Faria, Ana Catarina Vaz Pinheiro de Furtado (2023)
Background: Skinfold callipers are often used in clinical practice to estimate subcutaneous adipose tissue thickness. Recently, LipoTool emerged as a potential digital system to measure skinfolds, however comparisons with competing equipment are lacking. Aim: The aim of this study was to test the agreement between two competing skinfold callipers (digital and mechanical). Methods: The sample included 22 healthy male adult participants. A certified observer measured eight skinfolds twice using different skinfold callipers (digital and mechanical). Differences between equipment were tested using Wilcoxon signed rank test The distribution of error was examined using the normality test Results: Differences between skinfold callipers were significantly in five skinfolds: triceps (Z = -3.546; P < 0.001), subscapular (Z = -3.984; P < 0.001), suprailiac (Z = 3.024; P = 0.002), supraspinale (Z = 3.885; P < 0.001), abdominal (Z z=−2.937; P = 0.003), thigh (Z = -2.224; P = 0.026) and calf (Z = -2.052; P = 0.040). Differences between callipers were constant. Conclusions: Mechanical and digital callipers tended to record different values of skinfold thickness. Clinical examination should consider equipment-related variation in fat mass estimation.